REPRESENTATION OF THE RUSSIAN LINGUISTIC PICTURE OF THE WORLD IN PROVERBS WITH THE CONCEPT OF "HONOR" (Intent Research Scientific Journal, 2024)
This article is devoted to the analysis of the Russian linguistic picture of the world, which finds its representation in a small genre of oral folklore - proverbs. Proverbs with the concept of "honor" were chosen as the research material.